2019
DOI: 10.1097/md.0000000000016343
|View full text |Cite
|
Sign up to set email alerts
|

High BRAFV600E mutation frequency in Chinese patients with papillary thyroid carcinoma increases diagnostic efficacy in cytologically indeterminate thyroid nodules

Abstract: To estimate the BRAFV600E mutation frequency in Chinese patients with papillary thyroid carcinoma (PTC), and the diagnostic value of BRAFV600E mutation status in thyroid nodules with indeterminate TBSRTC categories. A total of 4875 consecutive samples for thyroid ultrasound-guided fine-needle aspiration cytology (FNAC) and BRAF V600E mutation analysis were collected from patients at Jiangsu Province Hospital on Integration of Chinese and Western Medicine. Among all the cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…In our verification cohort, the mutation frequencies of BRAF, TP53, MSH3, and MSH6 were 45.31% (29/64), 34.38% (22/64), 7.81% (5/64), and 12.50% (8/64), respectively, which did not fully consistent with our WES results. This is probably the reason for the different samples and other factors, but it was within the range of mutation frequency reported in the previous studies 6 , 19 . We also found that in the 23 PTCs samples, BCR, CREB3L1, and MSH6 underwent frameshift changes, a type of variation likely to affect the structure and function of these 3 gene products in the PTCs.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In our verification cohort, the mutation frequencies of BRAF, TP53, MSH3, and MSH6 were 45.31% (29/64), 34.38% (22/64), 7.81% (5/64), and 12.50% (8/64), respectively, which did not fully consistent with our WES results. This is probably the reason for the different samples and other factors, but it was within the range of mutation frequency reported in the previous studies 6 , 19 . We also found that in the 23 PTCs samples, BCR, CREB3L1, and MSH6 underwent frameshift changes, a type of variation likely to affect the structure and function of these 3 gene products in the PTCs.…”
Section: Resultssupporting
confidence: 85%
“…Several important mutated genes, such as BRAF, TP53, MSH3, and MSH6, were selected to verify the mutation frequency, and found that the cohort verification results were not completely consistent with the results obtained by the WES. We believe that different samples, sampling conditions, operating procedures, and other factors may lead to the inconsistent results, but the mutation frequency is within the range reported previously 6 , 19 . Our verification cohort, at least to some extent, supported the authenticity of the somatic mutation profiling.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Both genetic and environmental factors act on thyroid cells and ultimately lead to the transformation of normal thyroid cells into tumor cells. During PTC pathogenesis, some critical genes (including BRAF, RET, KRAS, and PI3KCA) through mutation or chromosomal translocation continuously activate their dependent downstream signaling pathways, such as mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K)/AKT, nuclear factor-κB (NF-κB), and Notch-1, and thereby lead to cellular proliferation, migration, invasion, and angiogenesis [15][16][17]. Recently, emerging clinical trials and experimental researches also demonstrated that some noncoding RNA expressions, such as miRs-21, -34b, -221/222, lncRNA ATB, lncRNA H19, lncRNA HOXA-AS2, circITCH, and circZFR, showed significant association with aggressive clinicopathologic feature in PTC, including tumor size, lymphovascular invasion, lymph node metastases, and presence of BRAF V600E mutation [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The BRAF V600E mutation, the T1799A transverse point mutation of BRAF that results in a valine-to-glutamic acid change in codon 600, which is the most common genetic alteration in PTC, was initially found in melanoma (8) and subsequently in other human cancers, including colorectal (9) and thyroid cancers (10). Studies have confirmed that the expression of the BRAF V600E mutant protein could constitutively activate the mitogen-activated protein kinase (MAPK) signaling pathway, which increases the recurrence and disease-specific mortality of PTC (11,12). This mutation constitutively activates the BRAF kinase and subsequently the MAPK signaling pathway (13,14).…”
Section: Introductionmentioning
confidence: 99%